PGV-1 decreases angiogenic factor (VEGF and COX-2) expression on T47D cell induced by estrogen - Meiyanto, Edy; Melannisa, Rosita; Da'i, Muhammad (Indonesian Journal of Pharmacy, 2006)
Breast cancer is the most common cancer occurring in women after cervix cancer in Indonesia. Tumor metastasis is the major cause of mortality in breast cancer. For a tumor cell to metastasize effectively, it must induce angiogenesis. 17 β-estradiol has been shown to stimulate the proliferation and angiogenesis of breast cancer cells which express estrogen receptor (ER), T47D (human breast cancer cell line). In the present study Pentagamavunon-1 or PGV-1 [2,5-bis-(4’-hydroxy-3’,5’-dimethylbenzylidene)-cyclopentanone], an analogue of curcumin [1,7-bis-(4’-hydroxy-3’-methoxyphenyl)-1,6-heptadiena-3,5-dion], were tested on their cytotoxicity and suppression effect on angiogenic factors (i.e. VEGF and COX-2) on the breast cancer cell lines (T47D) induced by 17 β-estradiol 10-8 M. The results showed that PGV-1 performed cytotoxicity effect againts T47D cells with IC50 values 3,16 μM. This was more potent than curcumin (IC50 = 19,05 μM). PGV-1 5 μM and curcumin 20 μM decrease VEGF and COX-2 expression. These results suggest both compounds possessed antiangio-genic potensial.Key words : PGV-1, curcumin, 17 β-estradiol, angiogenesis